KESEHATAN MENTAL SISWA YANG BERPACARAN DI SMK MUHAMMADIYAH 2 PEKANBARU - Mhd Algifari Mhd Algifari; Tri Umari; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: At this time many students and students are dating so that it has an impact on the learning process of these students, besides that dating behavior exacerbates the mental health of students in school which can interfere with their minds and minds. This study aims to determine the mental health of dating students and to determine the mental health of students in terms of psychological aspects and social aspects. This research is also useful as a contribution to the thoughts of the duinia of education and can increase the treasury of science, especially in the science of guidance and counseling related to the mental health of students who are dating. Descriptive research method with a quantitative approach to understanding the mental health behavior of students dating. The population of this study were all class X students who were dating with a sample of all students who were dating at school. The data used is data about the mental health of students who are dating using an instrument in the form of a closed questionnaire. Based on the psychological aspects of mental health, the dating students are categorized as not healthy and based on the social aspects of mental health the dating students are categorized as healthy.Keywords: Mental Health, Dating